2002
DOI: 10.4049/jimmunol.168.12.6412
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Activates Mast Cells Through the Collaborative Interaction with Lysophosphatidylserine Expressed on the Membrane Surface of Activated Platelets

Abstract: Effect of nerve growth factor (NGF) on platelet-associated mast cell activation was investigated. Although neither NGF alone nor platelets alone induced significant 5-hydroxytriptamine (5-HT) release from rat peritoneal mast cells, marked 5-HT release was detected when costimulated with NGF and calcium ionophore-activated platelets. This response reached maximal levels as early as 5 min after the initiation of the coincubation and was completely blocked by anti-NGF Ab or by an inhibitor for a tyrosine kinase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 52 publications
2
49
1
2
Order By: Relevance
“…This is consistent with observations made by Guhl et al who found that LAD2 production of TNF was only partially NK1R dependent even though LAD2 express mRNA for NK1R and NK2R. 36 Consistent with rodent mast cells, [50][51][52] we have shown that human mast cells express NK1R, NK2R and NK3R on their cell surface and SP may activate human mast cells via one or more of these receptors. However, because the SP-P-T inhibitor only partially blocked SP's effect, SP triggering of mast cells may also involve insertion of the amphiphilic SP molecule into the cell membrane, thus enabling direct activation of G proteins.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with observations made by Guhl et al who found that LAD2 production of TNF was only partially NK1R dependent even though LAD2 express mRNA for NK1R and NK2R. 36 Consistent with rodent mast cells, [50][51][52] we have shown that human mast cells express NK1R, NK2R and NK3R on their cell surface and SP may activate human mast cells via one or more of these receptors. However, because the SP-P-T inhibitor only partially blocked SP's effect, SP triggering of mast cells may also involve insertion of the amphiphilic SP molecule into the cell membrane, thus enabling direct activation of G proteins.…”
Section: Discussionsupporting
confidence: 81%
“…Lyso-PS Are Abundant Modified PS Species Generated in Neutrophils Stimulated to Activate the NADPH Oxidase-The signaling potential of lyso-PS was first recognized in its description as a potent mast cell secretagogue, and it has subsequently been given signaling roles in other settings (20,21,39,55,56). Here, we have shown that lyso-PS species were generated in vitro and in vivo as major modified PS species in neutrophils stimulated to activate the NADPH oxidase.…”
Section: Discussionmentioning
confidence: 81%
“…Of note, biological activities, both in vitro and in vivo, have been described previously for lyso-PS and lyso-PE. Lyso-PS has been shown to stimulate calcium flux in ovarian and breast cancer cell lines (48), leukemia cells (42), mast cells (49), and fibroblasts (43), but in other instances has had no biological effect when compared with lyso-PC (7,42). Although a lyso-PS-specific GPR34 has been recently identified in mast cells (50), its limited tissue distribution makes it unlikely to have mediated many effects previously reported for lyso-PS.…”
Section: Discussionmentioning
confidence: 99%